The occurrence of non-native tubenose goby Proterorhinus semilunaris in the pelagic 0+ year fish assemblage of a central European reservoir - Vašek, M; Jůza, T; Cech, M; Kratochvíl, M; Prchalová, M; Frouzová, J; Ríha, M; Tušer, M; Seďa, J; Kubečka, J (Journal of fish biology, 2011)
In July 2008, early juvenile tubenose goby Proterorhinus semilunaris were found in nocturnal pelagic waters of the Vranov Reservoir, Czech Republic. Presence of benthic-living prey in the guts of these fish suggested migration between benthic and pelagic habitats.
Keywords: Animals; ekosystém; Population Density; Biodiversity; Ecosystem; gastrointestinální obsah; zavlečené druhy; Česká republika; Czech Republic; Diet; Introduced Species; hustota populace; zvířata; Gastrointestinal Contents; Perciformes; dieta; biodiverzita